Empirical approaches to improving the use of DNA in crime scene investigative practice - Smith, Paul A. (International journal of police science & management, 2017)
This article reports on a collaborative project that explored the targeted use of swabbing evidence sources which, up until now, have not been routinely recovered or utilised for DNA analysis. All genres of the forensic portfolio have undergone significant changes driven by economic, political and technological influencers, which have resulted in an array of interpretations on its frontline delivery, often based on local requirements. The approach reported here pertains to a research project bringing together a collaborative team of researchers, representing practitioners and academics, working in conjunction with forensic service providers. The project reviewed the process of swabbing glove marks at crime scenes, comparing the methods used with DNA profiling outcomes. The findings showed significant benefits in regards to DNA outcomes, providing six detections over a four-month period that were attributable to the swabbing of the glove marks. Furthermore, the study provided key data to guide practice and crime scene methods to meet new operational requirements.